12-Molybdophosphoric acid supported on titania: A highly active and selective heterogeneous catalyst for the transesterification of dimethyl carbonate and phenol. (22nd December 2015) - Wang, Songlin; Tang, Rongzhi; Zhang, Yuanzhuo; Chen, Tong; Wang, Gongying
Abstract: 12-Molybdophosphoric acid supported on titania (HPMo/TiO2 ) was prepared by one-step in situ method and first used to catalyze the transesterification of dimethyl carbonate and phenol to diphenyl carbonate, which exhibited excellent catalytic activity. The highly dispersed HPMo and stable Keggin structure played a significant role for the excellent catalytic performance of HPMo/TiO2 . With the conditions of weight ratio of HPMo to TiO2 of 1:1, calcined temperature of 300 °C, catalyst amount of 0.6 g and reaction time 10 h, the phenol conversion and transesterification selectivity reached 50.4% and 99.4%, respectively. Moreover, after four consecutive runs, the phenol conversion slowly decreased from 44.7% to 29.5%, and the transesterification selectivity maintained at 99%. The characterization of XPS and FT-IR presented that the transformation of Mo 6+ to Mo 5+ and the adsorption of reaction intermediate were the key factors for the decrease of catalytic activity. Highlights: HPMo/TiO2 was first prepared by one-step in situ method. HPMo/TiO2 revealed superior catalytic activity to other heterogeneous catalysts reported. Highly dispersed HPMo and Keggin structure played significant role for the excellent catalytic performance. The transformation of Mo 6+ to Mo 5+ decreased the catalytic activity.